Myth and History in the Historiography of Early Rome - Cornell, Tim,; Meunier, Nicolas L. J.,; Miano, Daniele, (Classical Studies E-Books Online, Collection 2023., 2023)
The histories of early Rome written in antiquity by the likes of Livy and Dionysius of Halicarnassus include many sensational stories, from the she-wolf suckling the twins to the miraculous conception of Servius Tullius and the epiphany of the Dioscuri at Lake Regillus. Even the more sober parts of the narrative are of dubious historicity, and certainly include a good deal of rhetorical invention, aetiologies and folktales. The essays composing this volume attempt to analyse these stories to explore the porous boundaries and the hybrid borrowings between myth, history and historiography, and the limits of historical knowledge.